Conceptual framework for corporate governance in crisis period on example of hospitality industry in Latvia (Economics and region, 2021)
The pandemic caused by COVID-19 has caused a crisis in all spheres of life, there are many restrictions, including on crossing national borders and moving within one country. To limit the spread of the pandemic, many international measures have been adopted that have had a far-reaching, even catastrophic impact on tourism and the hospitality business. Many hotels around the world are in danger of bankruptcy. The topic of this study: impact of COVID-19 to the hospitality industry in Latvia and related crisis management measures. The question of the study: how does spread of COVID-19 pandemic impact hospitality industry in Latvia and how to evaluate  crisis management measures implemented in that area of business with an aim to minimize mentioned impact?The authors have analyzed the conceptual foundations of anti-crisis management in general, taking into account the current situation in the hospitality industry of Latvia in the context of the crisis caused by COVID-19 in particular. All market economy actors operating at the macro and micro levels, depending on the phase of the economic cycle, use different systems and strategies to ensure their sustainability. So A. Belyaev in the context of the crisis considers management as a process of financial recovery of the company, i.e. the author considers this process only at the level of an economic unit (micro level). This definition is flawed, since the author narrows the concept of crisis in it, without indicating the reason for its formation, describing in detail the process of recovery of the company. The purpose of the described by authors algorithm is to step-by-step optimize the actions to overcome the crisis at the macro level, which then reduces the probability of its occurrence and the severity of the processes taking place in it.
Keywords: crisis; management; hospitality industry; COVID-19